Pyrone derivatives from the soil fungus Fusarium solani PSU-RSPG37 - Kongkiat Trisuwan (2018)
Fusarpyrones A (1) and B (2), two new pyrone derivatives, were isolated from the soil fungus Fusarium solani PSU-RSPG37 together with eight known compounds, anhydrofusarubin, fusarubin, 5-hydroxy-8-methoxy-2,4- dimethylnaphtho[1,2,b] furan-6,9-dione, 2,3-dihydro-5-hydroxy-8-methoxy-2,4- dimethylnaphtho[1,2,b]furan-6,9-dione, javanicin, fusalanipyrone, p-hydroxyacetophenone, and tyrosol. The cytotoxic, antimalaria, and antimycobacterial activities of isolated compounds were examined. © 2013 Phytochemical Society of Europe. Published by Elsevier B.V. All rights reserved.